ANALISIS KOEFISIEN PENGALIRAN PADA HULU DAS BATANG KURANJI DENGAN MENGGUNAKAN CITRA LANDSAT 8 OLI - Rifky Putera Putera (Jurnal Pembangunan Nagari, 2020)
ABSTRACT Physical development of watershed impacted to debit flow and coefficient run off, thusan accurate method needs to collect the land cover information. Remote sensing as the quickly and easily technique is helpful to provide land cover informationat Kuranji watershed. This study aims to analyze the land cover change to runoff coefficient at the upstream Kuranji watershed in 2017 and 2018. The resultwasanalyzed by using OLI Landsat 8 (Quantum GIS software) with supervised classification methods to classify each class of land cover. Interpretation of OLI 8 Landsat image data at the upstream Kuranji Watershed showed that increasingof land cover change: the forest area283.92 Ha,settlement land 35.06 Ha, paddy field 27 Ha and decreasing area:mixed dry land agriculture 93.68 Ha, bare-land 3.16 Ha, shrub 277.43 Ha and garden area 190.95 Ha.. Land use change ​​affect the average value of runoff coefficientin 2017 (0.31) and 2018 (0.30). So, it is highlighted that the ability of infiltration at the upstream Kuranji watershed is getting better. Keywords:Kuranji Watershed, Land Cover, Landsat, Runoff Coefficient